Association of low back pain with presenteeism in hospital nursing staff - Yokota, Junpei (J Occup Health, 2019)
OBJECTIVES: Chronic low back pain (LBP) is known to cause various disorders compared with acute LBP. However, there was no study evaluating presenteeism due to LBP divided into subcategories by the duration of LBP. Therefore, this study aims to investigate the relationship between acute or chronic LBP and presenteeism in hospital nursing staff. METHODS: Overall, 1100 nurses filled in a questionnaire on basic attributes, LBP symptoms, depression symptoms, and work productivity. The subjects were divided into three groups based on the period of LBP and the compared work productivity. Work Limitation Questionnaire Japanese version (WLQ‐J) was used for the assessment of work productivity. The effects of acute and chronic LBP on presenteeism were evaluated through multiple regression analysis models. RESULTS: In total, 765 subjects, without missing values, were included. The overall prevalence of LBP was 64.6% (acute LBP 47.5%, chronic LBP 17.1%). On multiple regression analysis, acute pain and presenteeism were not associated. Conversely, chronic LBP was associated with time management (adjusted β = −2.3, 95% CI: −4.5 to −1.1), mental‐interpersonal relationship (adjusted β = −2.8, 95% CI: −5.1 to −0.6), and output (adjusted β = −2.7, 95% CI: −5.4 to 0.0) after adjustment for sex and career years. When depression was included in the adjustment factors, chronic LBP and WLQ subscales were not associated. CONCLUSIONS: It became obvious that Chronic LBP in nurses was significantly related to time management, mental‐interpersonal relationship, and output. The importance of preventing a decline in work productivity by taking precautions to prevent chronic LBP and depression was suggested.